ANALISIS PENGARUH DIFERENSIASI PRODUK, KUALITAS PELAYANAN, DAN CITRA MEREK TERHADAP KEPUTUSAN KONSUMEN MENGGUNAKAN JASA PERBANKAN SYARIAH (STUDI KASUS PADA BANK SYARIAH MANDIRI KOTA SEMARANG) - Ramdhani Harri Pratama; Indi Djastuti (JURNAL STUDI MANAJEMEN ORGANISASI, 2015)
In this globalization era business competition is very tight. It does not only apply globalbusiness, but it is also feel on business competition in Indonesia. This applies to all areasof business, including in the field of banking specifically for syariah banking. BankSyariah Mandiri present, perform, and grow as the bank that combine idealism with thebusiness of islamic values that underlie its operations, and in the field of islamic bankingbank the company sharia to be set hope up to have a good performance and attractpeople to use the services of islamic banking which is managed by bank syariah mandiri.The purpose of this research is to find out the effect of product differentiation, qualityservice, and brand image toward the purchasing decision. This research is descriptiveresearch that describes the related objects to common purchasing decision.Population of this research is the residents all over Semarang who use syariah bankingservice at Bank Syariah Mandiri Semarang. Sample of this research is 100 respondentswho use service at Bank Syariah Mandiri Semarang, taken by accidental sampling. Thedata is collected by spreading questionnaires and interview.The result of the research shows that all of independent variables (productdifferentiation, quality service, and brand image) have positively and significant affectpurchasing decision of Bank Syariah Mandiri as dependent variable. It means thataccording to the consumers, the three independent variables are considered important todecide whether to purchase Bank Syariah Mandiri.Keywords: product differentiation, quality service, brand image, purchasing decision